Geochemical and geochronological studies of Abor volcanic rocks of eastern Himalaya. Issue 2 (20th September 2021) - Baral, Upendra; Ding, Lin; Goswami, Tapos Kumar; Sarma, Mondip; Jan, MQ; Wang, Chao; Aminov, Jovid; Qasim, Muhammad; Bezbaruah, Devojit
Abstract : The Indian Plate began drifting northward after the Gondwana breakup and collided with the Eurasian Plate during the Early Cenozoic, resulting in the consequential development of the Himalayan–Tibetan Orogeny. Several microcontinents were rifted from Gondwana and amalgamated with the Indian Plate, resulting in magmatism along the continental margin. The Abor volcanic rocks (AVRs) in the eastern Himalaya represent one of such magmatism, the emplacement mechanism, and the timing of which is still a topic of debate. The AVR comprises mafic and silicic rocks; the present study concerns the petrography and geochemistry of the mafic rocks. U–Pb geochronology on three samples shows the weighted mean age of 130 ± 1 Ma, 143 ± 1.2 Ma, and 155 ± 16 Ma. Whole‐rock geochemistry of eight samples shows Mg# of 45.48 to 57.7, except for one sample with 37.4, variable contents of CaO (4.4–9.5 wt%), K2 O (0.1–2.6%), Lost on ignition (LOI) (0.9–3.6 wt%; average 2.4), and K2 O/Na2 O ratios (0.02–0.6 with a single one 1.0), Y/Nb (0.55–1.66, with one value of 2.44), and medium to high Zr/Nb (10.1–14.1) and Zr/Y (5.4–18.14). The Sr‐isotopic results from 11 samples show that the initial 87 Sr/ 86 Sr ratios vary between 0.7049 and 0.7110, and ε Nd ( t ) values range from +1.176 to −2.250. Geochemical and isotopic data suggest that the studied AVRs (mafic) are of subalkaline tholeiitic affinity. These volcanic rocks have continental intraplate characteristics and are sourced from the metasomatized mantle during the rifting event of the Indian subcontinent from Gondwana during Late Jurassic to Early Cretaceous. Abstract : Rifting of the Indian Plate from Gondwana lead to magmatism along the continental margin. The Abor volcanic rocks (AVRs) exposed along the Siang Valley, eastern Himalaya is one of such magmatism. The U–Pb geochronology, Sr isotopic results, and the whole rock geochemistry resemble the continental intraplate characteristics. Additionally, the AVRs are sourced from the metasomatized mantle during the rifting event of the Indian Plate from Gondwana at Late Jurassic to Early Cretaceous.